ANALISIS PROGRAM GREEN SCHOOL TERHADAP KESADARAN LINGKUNGAN SISWA KELAS IV MADRASAH IBTIDAIYAH SWASTA MA’HAD AL-ZAYTUN - Nada Daris Salam; Dewi Utami; Irvan Iswandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Environmental education from an early age is very important to overcome the ecological crisis caused by human behavior that lacks concern for nature conservation. This study aims to analyze the implementation of the green school program and its relationship with the environmental awareness of fourth-grade students at Madrasah Ibtidaiyah Swasta Ma'had Al-Zaytun, a school under the auspices of the Indonesian Islamic Boarding School Foundation that implements a boarding school system. Using a qualitative approach and descriptive method, data was collected through interviews, observations, and documentation from nine students selected through purposive sampling from three classes, as well as two teachers as supporting informants. Analysis was conducted using triangulation of sources, techniques, and time. The results of the study show that the green school program has been integrated into the madrasah culture, daily activities, and learning processes, thereby successfully fostering students' environmental awareness in cognitive, affective, and conative aspects. Support from teachers, peers, families, and the madrasah and Islamic boarding school communities reinforced the internalization of environmental awareness values, while the madrasah's culture of discipline became an important foundation for the program's sustainability. This study concluded that the green school program played a significant role in shaping environmentally friendly attitudes and behaviors in elementary school students.